Influencia de la fertilización sobre la producción de pimiento (Capsicum annuum L), En condiciones de invernadero - Ruiz Vargas, Wendy Francisca (2021)
In Ecuador, coffee is a product that is of relevant importance in the economic and social order for the agricultural sector due to the generation of foreign exchange and income that its export implies. In addition, during the last 15 years it has been among the first nine crops with the largest harvested area and is produced in 19 provinces of the country. The development of crops is based on the ability of the soil to provide the necessary amounts of nutrients for their proper development. The availability of these nutrients depends on several factors, being the content and quality of the organic matter present one of the most determining factors. This practical work aims to describe the use of compost and the role of soil organic matter in coffee production, in San José del Tambo, having as specific objectives: to quantify the amount of organic matter applied by producers in the area of study in coffee cultivation, determine the quality of the compost through its nutritional content and propose guidelines for the use of organic matter in coffee for the study area. For this analysis, the use of closed surveys was used as a methodology for coffee producers in the San José del Tambo area. A more precise knowledge of the content of organic matter and its quality could contribute to the formulation of better technical models for the management of coffee plantations. The investigations carried out have shown that by using organic fertilizers it is possible to obtain similar or better results than with chemical fertilizers, as long as the amounts applied are adequate.